2007
DOI: 10.1128/mcb.02314-06
|View full text |Cite
|
Sign up to set email alerts
|

cPGES/p23 Is Required for Glucocorticoid Receptor Function and Embryonic Growth but Not Prostaglandin E2 Synthesis

Abstract: A number of studies have identified cytosolic prostaglandin E 2 synthase (cPGES)/p23 as a cytoplasmic protein capable of metabolism of prostaglandin E 2 (PGE 2 ) from the cyclooxygenase metabolite prostaglandin endoperoxide (PGH 2 ). However, this protein has also been implicated in a number of other pathways, including stabilization of the glucocorticoid receptor (GR) complex. To define the importance of the functions assigned to this protein, mice lacking detectible cPGES/p23 expression were generated. cPGES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 82 publications
2
57
0
Order By: Relevance
“…Cells were seeded at a low density (about 20%) to allow for vigorous growth over a period of several days. In the absence of GA, p23-null cells grew slightly more slowly than wild-type cells as previously reported by others (31). However, in the presence of a relatively low dose of GA, p23-null cells rapidly stopped growing and died, whereas wild-type p23 cells even continued to grow for about 2 days and survived much longer (Fig.…”
Section: Resultssupporting
confidence: 85%
“…Cells were seeded at a low density (about 20%) to allow for vigorous growth over a period of several days. In the absence of GA, p23-null cells grew slightly more slowly than wild-type cells as previously reported by others (31). However, in the presence of a relatively low dose of GA, p23-null cells rapidly stopped growing and died, whereas wild-type p23 cells even continued to grow for about 2 days and survived much longer (Fig.…”
Section: Resultssupporting
confidence: 85%
“…A study of mPGES-2-deficient mice demonstrated that mPGES-2 was not essential for PGE 2 biosynthesis in peritoneal macrophages (32). Similar to mPGES-2, analysis of cPGES/p23-deleted mice suggests that cPGES is not required for PGE 2 synthesis (33). Taken together, these data suggest that increases in the level of mPGES-1 and its product, PGE 2 , in the spinal cord play a significant role in at least some of the sequential disturbances of motor performance in G93A mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, membrane prostaglandin E synthase-2 may contribute to the augmentation of endothelium-dependent contractions in the aorta of the aging rat. Recent gene knockout studies demonstrated that cytosolic prostaglandin E synthase is not required for the generation of prostaglandin E 2 in the mouse embryonic heart and liver, but it is required for the generation of prostaglandin E 2 in the embryonic mouse lung (18,24).…”
Section: Discussionmentioning
confidence: 99%